Development of a video-assisted thoracoscopic lobectomy program in a single institution: results before and after completion of the learning curve. Issue 1 (December 2016) - Gonfiotti, Alessandro; Bongiolatti, Stefano; Borgianni, Sara; Borrelli, Roberto; Jaus, Massimo; Politi, Leonardo; Tancredi, Giorgia; Viggiano, Domenico; Voltolini, Luca
Abstract Background The development of a video assisted thoracic surgery lobectomy (VATS-L) program provides a dedicated surgical team with a recognized learning curve (LC) of 50 procedures. We analyse the results of our program, comparing the LC with subsequent cases. Methods From June 2012 to March 2015, we performedn = 146 VATS major pulmonary resections:n = 50 (Group A: LC);n = 96 (Group B). Pre-operative mediastinal staging followed the National Comprehensive Cancer Network guidelines. All procedures were performed using a standard anterior approach to the hilum; lymphadenectomy followed the NCCN recommendations. During the LC, VATS-L indication was reserved to clinical stages I, therefore evaluated case by case. Results Mean operative time was 191 min (120-290) in Group A and 162 min (85-360) in Group B (p <0, 01). Pathological T status was similar between two Groups. Lymphadenectomy included a mean of 5.8 stations in Group A and 6.6 in Group B resulting in: pN0 disease: Group An = 44 (88 %), Group Bn = 80 (83.4 %); pN1: Group An = 3 (6 %), Group Bn = 8 (8.3 %); pN2: Group An = 3 (6 %), Group Bn = 8 (8.3 %). Conversion rate was: 8 % in group A (n = 4 vascular injuries); 1.1 % in Group B (n = 1 hilar lymph node disease). We registeredn = 6 (12 %) complications in Group A, n = 10 (10.6 %) in Group B. One case (1.1 %) of late post-operative mortality (90 days) was registered in Group B for liver failure. Mean hospital stay was 6.5 days in Group A and 5.9 days in Group B. Conclusions We confirm the effectiveness of a VATS-L program with a learning curve of 50 cases performed by a dedicated surgical team. Besides the LC, conversion rate falls down, lymphadenectomy become more efficient, indications can be extended to upper stages.